Research Trends of Problem Based Learning (PBL) Models to Improve Students' Critical Thinking Skills and Learning Outcomes (2016-2025): A Systematic Review - Fitratunisyah, Fitratunisyah; Bactiar, Imam; Jamaluddin, Jamaluddin (Balai Publikasi Indonesia, 2025)
This study examines the trend of the Problem Based Learning (PBL) model in improving critical thinking skills and student learning outcomes during the period 2016-2025. The PBL model is a learning model that involves students to solve a problem through the stages of the scientific method so that students can learn knowledge related to the problem and at the same time have the skills to solve problems. In learning, critical thinking is a high-level thinking skill that plays an important role in solving problems. Critical thinking is the ability to develop and explain arguments from data that is arranged into a complex decision or idea. Critical thinking is able to analyze data or information in a systematic way based on logic in investigating data or facts. This study aims to identify and analyze the Problem Based Learning (PBL) model to improve critical thinking skills and student learning outcomes. This research method is descriptive and analytical. The data used in this study were obtained from documents indexed by Google Scholar from 2016-2025 using publish or perish and dimension.ai. The data identified and analyzed were the types of publications, publication sources, and research titles on the PBL model to improve critical thinking skills and student learning outcomes that were widely cited. The data analysis method used bibliometric analysis assisted by VOS viewer software. The results of the study showed an increase in the number of publications from 2016 to 2020, with the peak of publications occurring in 2020 and a decline in 2021 to 2022. And there was an increase again in 2023 to 2024. In 2025 there was still a decline because the title was still rarely used. However, there are fluctuations that indicate challenges in this study. In addition, there are many types of publications in the form of article chapters, proceedings, edited books and monographs. However, the most common type of publication is articles, indicating a strong contribution from research in this field